Beyond the metaphor: the Social Solidarity Economy as a space for rebuilding the social fabric - Ríos y Valles Boysselle, Fernando; Cendejas Guízar, Josefina; Orozco Plascencia, José Manuel (Cooperativismo & Desarrollo, 2025)
This paper presents the results of research on the state of the art of the metaphor of the “social fabric,” with an emphasis on its link to the characteristics and contributions of the Social and Solidarity Economy (SSE) for its reconstruction. The findings highlight the potential of the social fabric to articulate new socioeconomic configurations based on solidarity and cooperation for the satisfaction of material needs and the expansion of public and private freedoms exercised ethically for good living. In this vein, multiple points of convergence are identified between the SSE and the (re)construction of the social fabric, highlighting the potential to weave new and alternative forms of sociality that, while resisting violence in the territories, generate and promote emancipatory forms of transition towards a post-capitalist society.